Western Influences and the Evolution of Medical Practices and Public Health in Pre-1932 Siam - Satchanawakul, Nattanee (FOYER: The Journal of Humanities, Social Sciences, and Education, 2024)
Western concepts, particularly scientific knowledge and medical technology, have profoundly influenced the evolution of modern Siam/Thailand. The introduction of "Western medicine and public health knowledge," especially the use of innovations, dramatically reduced sickness and mortality rates, contributing to a healthier population and, consequently, economic growth, by increasing the workforce. This intertwining of medical science with individual, community, societal, and state development marked a significant shift in Thai medical and public health practices. In truth, preventing mortality was a novel concept in Siam, largely introduced by missionaries who performed modern medical services along with their dissemination of religious teachings. The acceptance of Western technology led to transformative changes in medicine and public health, including advancements in treatment methods, tools, and pharmaceuticals, eventually culminating in the establishment of "Western-style hospitals." Furthermore, the early development of medical practices and public health in Siam was shaped by the cultural negotiation between Western influences and indigenous beliefs, particularly the concept of merit and charity. This research highlights how Western influence shifted medical and public health paradigms in Siam, laying the groundwork for modern healthcare practices in Thai society that came later.